Governança, custos e subsídios cruzados no sistema infraero - Eduardo P. S. Fiuza (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– A decree from 2000 - which created the Brazilian Civil Aviation Council (Conac) -, joint with a law from 2005 - which created the Brazilian Civil Aviation Agency (Anac) - rule that the former proposes to the President of the Republic a regulatory benchmark for the airport industry. The recent crisis in the aviation industry, including accusations of embezzlement of funds of the state-owned major airport owner (Infraero), gave rise to a movement for the review of the regulatory benchmark towards privatization. However, it is alleged that only a few airports run an accounting surplus, even though the ordinary accounts jeopardize this assessment. Based on accounting statements following the usual depreciation practices, we endeavor to test for cross-subsidies as suggested in the economic literature. Moreover, we discuss some aspects of Infraero`s management. According to one of the tests, only Guarulhos and Viracopos have not enjoyed cross-subsidies during the whole period. Under more flexible criteria, also Congonhas, Manaus, Navegantes, Fortaleza and Ilhéus would not be subsidized. Regarding the various revenue sources within Infraero, it is worth noting that aircraft movements' the ultimate role of an airport-are the activity that contributes the least to the firm's profitability. Although the flights may be subsidized by commercial revenues, Infraero claims that the tariffs are far below the international standard.
Keywords: L93; L25; L32; L51; 330